Genetic divergence and hybrid potential for yield and fiber quality in cotton (Gossypium hirsutum. L) - Anusha Ashok Hugar; Jayaprakash Mohan Nidagundi; Bashasab Fakrudin; Yogesh Lingappa Neelagiri; Sonnappa Muniswamy; Arunkumar C Hosamani; Soumya Chikkasiddaiah Hallasahalli; Mohamed A. Rashwan; Ihab Mohamed Moussa; Eman A. Mahmoud; Hosam O. Elansary; Kariyanna B (Journal of Natural Fibers)
Fiber trait is multigenic and each parent of the population carrying different genes aid in arriving at varied blend of association between yield and fiber quality traits. Eleven parental lines were crossed in half-diallel fashion to arrive at 55 hybrid combinations, which were evaluated under seven environments. The results manifested highly significant differences among the traits studied, indicating wide range of genetic diversity in the parental genotypes. Combining ability studies revealed parental genotypes SCS-PL-01, SCS-PL-04 as best general combiners for seed cotton yield; SCS-PL-04, SCS-PL-12, SCS-PL-51, SCS-PL-59 for fiber length; SCS-PL-51 for fiber strength and SCS-PL-02 for micronaire value. Genetic diversity of parental genotypes estimated using microsatellites was compared with SCA effects to understand the role of genetic distance (GD) in realizing the heterosis. Comparative characterization of parental genotypes indicated efficiency of capillary gel electrophoresis over metaphor agarose gel electrophoresis and could identify 55 unique bands. The study indicated predicting heterosis using GD estimates is competent when markers linked to the QTLs are used. Also, marker-assisted parental selection in combining ability studies would be a better approach in realizing potential crosses with high yield and fiber quality traits.